2022
DOI: 10.3390/antiox11091634
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Inhibition by PF06447475 Antagonist Modulates Early Neuronal Damage after Spinal Cord Trauma

Abstract: Spinal cord injury (SCI) is a devastating event followed by neurodegeneration, activation of the inflammatory cascade, and immune system. The leucine-rich-repeat kinase 2 (LRRK2) is a gene associated with Parkinson’s disease (PD), moreover, its kinase activity was found to be upregulated after instigated inflammation of the central nervous system (CNS). Here, we aimed to investigate the PF06447475 (abbreviated as PF-475) role as a pharmacological LRRK2 antagonist by counteracting pathological consequences of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Although the anti-inflammatory properties of LRRK2 inhibitors are starting to be considered as disease-modifying treatment for PD, little is known about the beneficial effects of targeting LRRK2-related neuroinflammation in preclinical models. In this regard, a few studies reported that LRRK2 kinase inhibition leads to an attenuation of neuroinflammation and neurodegeneration under pathological conditions [ 23 , 27 , 28 , 29 ], thus supporting the idea that lowering LRRK2 kinase activity has an anti-inflammatory effect and could be neuroprotective during the pathology. In this study, we further validated the modulation of LRRK2 kinase activity as a pharmacological intervention in diseased brains.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although the anti-inflammatory properties of LRRK2 inhibitors are starting to be considered as disease-modifying treatment for PD, little is known about the beneficial effects of targeting LRRK2-related neuroinflammation in preclinical models. In this regard, a few studies reported that LRRK2 kinase inhibition leads to an attenuation of neuroinflammation and neurodegeneration under pathological conditions [ 23 , 27 , 28 , 29 ], thus supporting the idea that lowering LRRK2 kinase activity has an anti-inflammatory effect and could be neuroprotective during the pathology. In this study, we further validated the modulation of LRRK2 kinase activity as a pharmacological intervention in diseased brains.…”
Section: Introductionmentioning
confidence: 82%
“…Accordingly, the Morari group reported that LRRK2 PF and MLi2 inhibitors protected from 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine (MPTP)-induced neurotoxicity and gliosis [28]. In addition to the PD-related state, lowering LRRK2 kinase activity has been shown to have anti-inflammatory properties even in a mouse model with spinal cord injury [27], thus supporting the idea that LRRK2 could be targeted and be beneficial for different brain diseases with an inflammatory component. Interestingly, in this study, we provide additional proof of the proinflammatory response's effects in preclinical models with pathological conditions linked to AD and PD, as well as the ability of LRRK2 kinase inhibition to attenuate them.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, a preliminary dose-response study was performed to obtain the experimental doses to be used. Based on previous in vivo studies, we chose PF-475 as the route of administration [ 12 , 14 ]. PF-475 was prepared in dimethyl sulfoxide (DMSO) and diluted with 0.9% saline to obtain a final DMSO concentration of 1%.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, LRRK2 affects protein synthesis and degradation, apoptosis, inflammation and oxidative stress, processes that trigger mTBI. It has been reported that inhibition of LRRK2 with the antagonist PF-475 alleviated neuronal apoptosis, brain oedema and neurological deficits induced by traumatic injury [ 11 , 12 ]. Moreover, pharmacological inhibitors of LRRK2 not only modulate neuronal cell death and neuroinflammation, but also prevent the behavioral defects in mice induced by controlled cortical impact injury (CCI) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess the degree of myelination/demyelination, staining with the LFB stain kit (#ab150675, Abcam, Cambridge, UK) was performed in the deparaffinized sections following the manufacturer's instructions [45]. In brief, midbrain sections were incubated in LFB solution at 56 • C O/N.…”
Section: Luxol Fast Blue (Lfb) Stainingmentioning
confidence: 99%